Full denture in patient with cleft palate - Vilchez Salazar, Ernesto (2014)
We report the rehabilitation of a total edentulous patient with cleft palate. Being a complex case involving one of the factors of stability (retention), we had to use materials with grater hydrophilicity to take impressions. The technique without pressure was used for primary impressions and technique of selective pressure (elastomer) for making the final impression; obtaining more intimate contact between the prosthesis and the mucosa, for better adhesion and cohesion. Completely relieved cuvettes were used to take impressions with a minimal pressure. The purpose of this treatment was to rehabilitate the masticatory system of total edentulous patient with cleft palate, unlike ordinary cases, the adaptation of the prosthesis to the mucosa should be intimate; maintaining the resilience of the mucosa and allowing good retention.